2021
DOI: 10.1080/14614103.2021.1959188
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and the Migration of a Pastoralist People c. 3500 cal. Years BP Inferred from Palaeofire and Lipid Biomarker Records in the Montane Western Ghats, India

Abstract: Human migration in response to climate change during the Holocene has been recorded in many regions of the world. The Todas are a pastoralist people who are believed to have colonized the higher elevations (>2000 m asl) of the Nilgiris in the Western Ghats, India, not earlier than about 2000 cal. yr BP. Vegetation shifts in response to changing climate in tropical montane forest-grassland mosaic of the Ghats have been well documented using stable carbon isotopes and pollen profiles; however, there have been no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…This could be due to gradually ameliorating hydrology (gradual, climate-initiated) or a disturbance to the shola leading to an unstable transition state (disturbance-initiated). The latter interpretation is supported by results from Kavil et al (2021) who studied sediments from a pit proximate to Core 1 and found charcoal at 22.1 ka. They also present Scanning Electron Microscopy images to show that the macrocharcoal has abundant woody and grass elements, an indicator that woody elements indeed were present at 22 ka (Figure 5 in Kavil et al (2021)).…”
Section: Interpreting the Divergent δ 13 C Profiles At Sandynallahmentioning
confidence: 53%
See 4 more Smart Citations
“…This could be due to gradually ameliorating hydrology (gradual, climate-initiated) or a disturbance to the shola leading to an unstable transition state (disturbance-initiated). The latter interpretation is supported by results from Kavil et al (2021) who studied sediments from a pit proximate to Core 1 and found charcoal at 22.1 ka. They also present Scanning Electron Microscopy images to show that the macrocharcoal has abundant woody and grass elements, an indicator that woody elements indeed were present at 22 ka (Figure 5 in Kavil et al (2021)).…”
Section: Interpreting the Divergent δ 13 C Profiles At Sandynallahmentioning
confidence: 53%
“…Why would Cores 1 and 2 that are only ~170 m apart in the same valley show such a major difference in past vegetation composition? What role do disturbances such as the fires reported by Kavil et al (2021) play in maintaining these vegetation states? We explore the various reasons that might have resulted in these patterns within the alternative stable states framework.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations